(untitled) (Società e diritti, 2018)
The juristic act is an exercise of juridical normative powers, that is recognized as such from the law of the State. It consists of categorical norms, that primarily provide relatively to cases of kind, creating, modifying or extinguishing juridical relationships. Such norms are inserted, as smaller and derived, in the widest normative whole of the law of the State. Key words: Ruleof Law, Autonomy, Juridical normative power